The Effect of Self-Compassion and Social Support on the Psychological Well-Being of Foster Children in Pekalongan City - Saputri, Nurshafilla Rizka; Sugiharto, Dwi Yuwono Puji; Mulawarman, Mulawarman (Jurnal Bimbingan Konseling, 2024)
Psychological well-being is significant for foster children since it reinforces them in going through critical and challenging times. In this way, the present study aimed at analyzing the effect of self-compassion and social support on the psychological well-being of foster children throughout Pekalongan City. It used an ex post facto method and involved 67 foster children selected using a proportionate stratified random sampling technique. The subjects’ data were collected using the scales of self-compassion, social support and psychological well-being for later analyzed using a multiple regression test. The self-compassion scale had 26 items with the coefficient value of 0.33 and reliability of 0.915. The social support scale had 27 items with the coefficient value of 0.334 and reliability of 0.889. Following the analysis, the findings indicated self-compassion had no effect on psychological well-being, social support affected the psychological well-being, and both self-compassion and social support explained the variants of psychological well-being by 33.8 % (R2 = .337). These findings have implications for community guidance and counseling in carrying out prevention and alleviation functions for teenagers in orphanages related to their psychological well-being.